2018
DOI: 10.3748/wjg.v24.i28.3130
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion treatment modulates the gut microbiota and immune function in a dextran sulphate sodium-induced colitis rat model

Abstract: Our findings suggest that moxibustion exerts its therapeutic effect by repairing mucosal tissue damage and modulating the gut microbiome and intestinal mucosal immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 51 publications
6
41
0
Order By: Relevance
“…Clinical and experimental studies have shown beneficial role of acupuncture and moxibustion in reducing IBD disease activity and inflammation [20][21][22]. Our previous studies also found that both EA and moxibustion have therapeutic effect on colitis rats [4,11,23].…”
Section: Introductionmentioning
confidence: 60%
“…Clinical and experimental studies have shown beneficial role of acupuncture and moxibustion in reducing IBD disease activity and inflammation [20][21][22]. Our previous studies also found that both EA and moxibustion have therapeutic effect on colitis rats [4,11,23].…”
Section: Introductionmentioning
confidence: 60%
“…In addition, the phyloseq package [ 30 ] was used to plot data and perform statistical analysis in R. Metagenome function was predicted by Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) software [ 31 ]. Metabolic pathways were aligned and translated from the gene catalog against the proteins (or domains) in the KEGG databases ( ).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental and clinical studies have shown that acupuncture is a safe and effective treatment, and a meta-analysis has shown that acupuncture is more effective than oral sulphasalazine in the treatment of IBD[ 65 ]. Moxibustion plays a therapeutic role by repairing mucosal tissue damage, regulating gut microbiota and improving intestinal mucosal immunity[ 66 , 67 ] and short-term (7 d) rather than long-term (14 d) moxibustion may significantly affect the gut microbiota[ 66 ]. Studies by Wei et al[ 68 ] have shown that both electroacupuncture and moxibustion can improve anxiety behaviors in patients with colitis, and its effect comes in part from improving the balance of the HPA axis.…”
Section: Microbiota-gut-liver-brain Axis and Ibdmentioning
confidence: 99%